Tourism Area Development Strategy Banda Naira Islands - Viqa Lamuda; Usama Ashmawi; Muhammad Sangadji (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine the development strategy for the Banda Naira Islands tourism area with a focus on the problem of developing tourism destination components and the strategy of the Technical Implementation Unit of the Tourism, Youth and Sports Service of Banda Naira District. Methodology: This type of research is descriptive qualitative. Key informants numbered four (4) people selected using purposive sampling techniques, and secondary informants numbered three (3) people using snowball sampling. Data collection methods were through observation, documentation, and interviews. Main Findings: The development of the Banda Naira Islands tourist destination has not been optimal even though it has great potential in marine, historical, and cultural tourism. The main obstacles include infrastructure, facilities, transportation, and management that have not been organized. With the SO (Strengths-Opportunities) strategy, institutional strengthening, collaboration, and integrated utilization of local potential are expected to increase the competitiveness and sustainability of the tourism area. Novelty/Originality of this study: This study offers a new approach in developing tourism areas in the Banda Naira Islands by utilizing the SO (Strengths-Opportunities) strategy that has not been optimally implemented before. The focus of this study is to identify specific strengths and opportunities in the Banda Naira Islands, such as the uniqueness of historical and cultural tourist attractions, as well as natural potential that has not been fully developed, and utilize them aggressively to attract more tourists.